TRTE Herbarium (TRTE) from University of Toronto Mississauga ... - Stefanovic, Sasa (University of Toronto Mississauga, 2012)
The TRTE Herbarium is administered and overseen by the Department of Biology at the University of Toronto at Mississauga. Our herbarium, founded in 1969, houses about 95,000 specimens of vascular plants, including the extensive collections of Paul F. Maycock and Peter W. Ball. Geographically, the herbarium’s main focus is on vascular plant specimens from Ontario, but important collections are also available from Québec and the Canadian high Arctic. Small quantities of specimens are available from all other regions of Canada, United States, Western Australia, New Zealand, and West Africa (Nigeria, Sierra Leone). Taxonomically, our herbarium is particularly strong in its representation of sedges (genus Carex), mainly from eastern Canada and, to a lesser extent, from elsewhere in Canada and the United States. ...